Preparation of Carboxymethyl Cellulose/Polyvinyl Alcohol Cryogels for the Removal of Methylene Blue Dye from Aqueous Media - Abakan, Ilkkan; Ozbilenler, Cahit; Usturk, Selma; Kerkuklu, Namik Refik; Gulcan, Hayrettin Ozan; Guran, Mumtaz; Gazi, Mustafa (Pleiades Publishing Ltd, 2024)
In this study ciprofloxacin-loaded carboxymethyl cellulose (CMC)/ polyvinyl alcohol (PVA) cryogel systems were prepared by using low molecular weight PVA. The high degree of segmental mobility of PVA molecules makes them more prone to form CMC/PVA cryogels via hydrogen bondings with CMC. Physically crosslinked gels were characterised by using Fourier-transform infrared spectroscopy (FTIR). Swelling results have shown that low molecular weight PVA had a fast-swelling rate and this can explain the fast release of ciprofloxacin within 30 min from CMC/PVA cryogels during release studies. Release of ciprofloxacin from the CMC/PVA cryogel system was the best fit to first-order release model with R-2 = 0.9980. It was found that the release exponent is lower than 0.45 and it is a good indication of quasi-Fickian diffusion, which means that ciprofloxacin can be released without swelling of the cryogel. Ciprofloxacin was found to have even better antimicrobial activity against E. coli than positive control as having a higher inhibition zone. In addition, CMC/PVA cryogels can be used for water treatment application to remove Methylene Blue (MB) dye from water and this was supported by adsorption kinetics and isotherm studies.
Keywords: Carboxymethyl cellulose (CMC); polyvinyl alcohol (PVA); ciprofloxacin; release kinetic; antibacterial activity